Increased atrial fibrillation risk in Parkinson's disease: A nationwide population‐based study. Issue 1 (3rd January 2021) - Han, Seokmoon; Moon, Inki; Choi, Eue‐Keun; Han, Kyung‐Do; Cho, Hae‐Chan; Lee, Seo‐Young; Yang, Seokhun; Kwon, Soonil; Choi, You‐jung; Lee, Hyun‐Jung; Lee, Euijae; Lee, So‐Ryung; et al.
Abstract: Objective: Parkinson's disease (PD) is the second most common neurodegenerative disorder associated with various morbidities. Although the relationship between cardiovascular disease and PD has been studied, a paucity of information on PD and atrial fibrillation (AF) association exists. Thus, we aimed to investigate whether patients with PD have an increased risk of AF. Methods: This study included 57, 585 patients with newly diagnosed PD (≥40‐year‐old, mean age 69.7 years, men 40.2%) and without a history of AF from the Korean National Health Insurance Service (NHIS) database between 2010 and 2015. Furthermore, an equal number of age‐ and sex‐matched subjects without PD were selected for comparison. The primary outcome was new‐onset AF. Results: During the mean follow‐up period of 3.4 ± 1.8 years, AF was newly diagnosed in 3, 665 patients. A significantly higher incidence rate of AF was noted among patients with PD than among patients without PD (10.75 and 7.86 per 1000 person‐year, respectively). Multivariate Cox‐regression analysis revealed that PD was an independent risk factor for AF (hazard ratio [HR]: 1.27, 95% confidence interval [CI]: 1.18–1.36). Furthermore, subgroup analyses revealed that AF risk was higher in the younger age subgroups, and compared with the non‐PD group, the youngest PD group (age: 40–49 years) had a threefold increased risk of AF (HR: 3.06, 95% CI: 1.20–7.77). Interpretation: Patients with PD, especially the younger age subgroups, have an increased risk of AF. Active surveillance and management of AF should be considered to prevent further complications.